Study of an active antimicrobial system using a bio-switch concept - Muhammad, Ida Idayu; Razali, Firdausi; Md. Salleh, Liza (Universiti Teknologi Malaysia, 2005)
In response to the dynamic changes in current consumer demand and market trends, the area of Active Packaging (AP) is becoming increasingly significant. An Antimicrobial Active Packaging can be made by incorporating and immobilizing antimicrobial (AM) agents into food packages and applying a bio-switch concept. By that, the mechanism of antimicrobial release between the developed bio-switch particles and the stimulus of a microbial contamination can be studied. The objective of this research is to develop a starch-based film incorporated with antimicrobial agents consisting of lysozymes, lauric acid, nisin and EDTA (chelating agent). The effectiveness of the AM film towards inhibition of microbial activity was evaluated. Clear zones formed on the film appearance showed the combination of both AM agents gives good inhibition to the growth of E. coli and B. subtilis with satisfying inhibition rate. With the advent of new polymer materials and antimicrobials, the development of AP could prolong the shelf life of food and reduce the risk of foodborne illness caused by microbial contamination.